Parvalbumin increases in the medial and lateral geniculate nuclei of aged rhesus macaques. - Daniel T Gray; Megan L. Rudolph; James R. Engle; James R. Engle; Gregg H Recanzone; Gregg H Recanzone (Frontiers in Aging Neuroscience, 2013)
Subcortical auditory structures in the macaque auditory system increase their densities of neurons expressing the calcium binding protein parvalbumin (PV) with age. However, it is unknown whether these increases occur in the thalamic division of the auditory system, the medial geniculate nucleus (MGN). Furthermore, it is also unclear whether these age-related changes are specific to the macaque auditory system or are generalized to other sensory systems. To address these questions, the PV immunoreactivity of the medial and lateral geniculate nuclei (LGN) from seven rhesus macaques ranging in age from 15 to 35 was assessed. Densities of PV expressing neurons in the three subdivisions of the MGN and the six layers of the LGN were calculated separately using unbiased stereological sampling techniques. We found that the ventral and magnocellular subdivisions of the MGN and all six layers of the LGN increased their expressions of PV with age, although increases in the MGN were greater in magnitude than in the LGN. Together, these results suggest that the MGN shows age-related increases in PV expression as is seen throughout the macaque ascending auditory system, and that the analogous region of the visual system shows smaller increases. We conclude that, while there are some similarities between sensory systems, the age-related neurochemical changes seen throughout the macaque auditory system cannot be fully generalized to other sensory systems.